2019
DOI: 10.1002/aic.16563
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and quantitative design of a flow‐guiding sieve tray by computational fluid dynamics

Abstract: An evolution of the traditional sieve tray, the flow‐guiding sieve tray (FGST), has been utilized in many separation processes, especially for handling viscous systems. The objectives of this work are to optimize the design process of FGSTs and realize the full potential of their separation performance. A computation fluid dynamic (CFD) model that incorporated the modified interphase momentum transfer term was developed. Simulated measures of hydrodynamic performance, such as pressure drop, weeping, entrainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Solari and Bell reported nearly identical velocities at the upstream and downstream of the flow (on a line with the same Z coordinates); thus, the obtained velocities in this study were compared with the linear mean of upstream and downstream velocities reported by Solari and Bell. As mentioned previously, we assumed a parabolic liquid velocity profile, [15,21,27] while Solari and Bell simply ignored the profile. Figure 3 shows a view of Solari and Bell's tray along with a horizontal cross section of the simulated trays (the red lines indicate the positions where average liquid velocities were measured).…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Solari and Bell reported nearly identical velocities at the upstream and downstream of the flow (on a line with the same Z coordinates); thus, the obtained velocities in this study were compared with the linear mean of upstream and downstream velocities reported by Solari and Bell. As mentioned previously, we assumed a parabolic liquid velocity profile, [15,21,27] while Solari and Bell simply ignored the profile. Figure 3 shows a view of Solari and Bell's tray along with a horizontal cross section of the simulated trays (the red lines indicate the positions where average liquid velocities were measured).…”
Section: Validationmentioning
confidence: 99%
“…The results were in good agreement with experimental data. Other studies [9][10][11][12][13][14][15][16][17][18][19][20][21] have investigated the hydrodynamics, mass transfer, and efficiency of sieve trays using CFD. Some scholars studied the hydrodynamic simulation of valve trays.…”
Section: Introductionmentioning
confidence: 99%
“…Distillation columns are essential equipment to separate liquid mixtures widely used in chemical, petroleum, pharmaceutical, and environmental industries [1][2][3][4]. The performance of the valve tray can directly affect the raw material handling capacity and product quality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stability factors were calculated using the dry pressure drop and the clear liquid height for the two trays and compared based on the weep rates. Many researchers have already studied the hydraulics of trays by CFD or experiments [24][25][26][27][28]. However, there are many issues about industrial trays and towers that have not yet been fully investigated.…”
Section: Introduction and Previous Workmentioning
confidence: 99%